2015
DOI: 10.1007/s11046-015-9898-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Bruker Matrix-Assisted Laser Desorption–Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) System for the Identification of Clinically Important Dermatophyte Species

Abstract: Dermatophytes can invade the stratum corneum of the skin and other keratinized tissues and are responsible for a broad diversity of diseases of skin, nails and hair. Although the standard identification of dermatophytoses depends on macroscopic and microscopic characterization of the colonies grown on special media, there are a number of limitations owing to intraspecies morphological variability, atypical morphology or interspecies morphological similarity which entails improvement in the identification metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 23 publications
4
29
1
3
Order By: Relevance
“…We found only 14 out of the 149 strains with a LS below our defined thresholds but above should prompt clinicians to further assess the animal source of the infection. 4 Contrasting with previous findings, 8,9,21,22 Table S1). Of interest, a similar discrepancy was also obtained with B-MSPL which suggests that it is strain dependent.…”
Section: T Mentagrophytes and T Interdigitale Was Difficult By Maldcontrasting
confidence: 87%
See 1 more Smart Citation
“…We found only 14 out of the 149 strains with a LS below our defined thresholds but above should prompt clinicians to further assess the animal source of the infection. 4 Contrasting with previous findings, 8,9,21,22 Table S1). Of interest, a similar discrepancy was also obtained with B-MSPL which suggests that it is strain dependent.…”
Section: T Mentagrophytes and T Interdigitale Was Difficult By Maldcontrasting
confidence: 87%
“…This is of clinical relevance because these latter cannot be differentiated using common methods but require ITS gene sequencing and identification of zoophilic T. mentagrophytes should prompt clinicians to further assess the animal source of the infection . Contrasting with previous findings, we could discriminate T. violaceum from T. rubrum and T. soudanense by MALDI‐TOF/MS if cultures were made on PDA. However, T. benhamiae was not easily identified because low LS were frequently obtained irrespective of the medium used for subculture.…”
Section: Discussionmentioning
confidence: 66%
“…For many years, the gold standard for diagnosis of superficial fungal infections has been direct microscopy often performed by the clinician, and culture sometimes supplemented by histopathology. Since the first dermatophyte polymerase chain reaction (PCR) was developed in 1996 an array of new molecular based methods for fungal identification have been developed with different PCR techniques and lately, matrix assisted laser desorption/ionization – time of flight (MALDI‐TOF) mass spectrometry has also been used . Because special equipment is required to perform molecular diagnostics the analysis is performed at specialized mycological or microbiological laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Although these methods can provide accurate results, they are expensive, require specialized equipment or expertise, and are not commonly available in clinical laboratories. In the present review, findings from the 10 studies (23)(24)(25)(27)(28)(29)(30)(31)(32)(33) shown in Table 1 indicate that before MALDI-TOF MS testing, only one study identified isolates via conventional phenotypical analyses (33), whereas almost all the remaining studies also sequenced all their isolates, and in two studies, only molecular biology analyses of the isolates were undertaken (27,28). This supports the idea that the overall high level of accuracy of MALDI-TOF MS-based mold identification shown in these studies might not be overestimated.…”
Section: Mold Identification By Maldi-tof Ms: Is It Really a History mentioning
confidence: 92%
“…A more recent evaluation of the performance of the Bruker Biotyper system showed that MALDI-TOF MS provided correct genus-level and species-level identifications for 96.8% (122/126) and 87.9% (113/126) of dermatophyte isolates, respectively, using a supplemented database (the MALDI Biotyper Support Library, i.e., created by adding spectra from 10 reference dermatophyte strains) and decreased score values (33). Expectedly, rates of correct genus-level and species-level identifications of 51.6% and 13.5% were found when MALDI-TOF MS analyses were done by using the original database (MALDI Biotyper Library [MBL] version 3.1.2.0) and manufacturer-recommended score values (33).…”
Section: Rhizopus-lichtheimia Species Previous Reports On the Maldi-mentioning
confidence: 99%